A Phase I Study of the Anti‐Idiotype Vaccine Racotumomab in Neuroblastoma and Other Pediatric Refractory Malignancies. Issue 12 (7th July 2015) - Cacciavillano, Walter; Sampor, Claudia; Venier, Cecilia; Gabri, Mariano R.; de Dávila, María T.G.; Galluzzo, Maria L.; Guthmann, Marcelo D.; Fainboim, Leonardo; Alonso, Daniel F.; Chantada, Guillermo L.
<x xml:space="preserve">Abstract</x> Background Pediatric neuroectodermal malignancies express N‐glycolylated gangliosides including N‐glycolyl GM3 (NeuGcGM3) as targets for immunotherapy. Procedure We evaluated the toxicity and maximum tolerated dose and immunological response of racotumomab, an anti‐idiotype vaccine targeting NeuGcGM3 through a Phase I study enrolling children with relapsed or resistant tumors expressing NeuGcGM3. Materials and methods Drug dose was escalated to three levels (0.15–0.25–0.4 mg) of racotumomab administered intradermally. Each drug level included three patients receiving a total of three doses, every 14 days. A confirmation cohort was added to the highest dose level. Antibody response was assessed upon study entry and at 4‐week intervals for at least three immunological determinations for each patient. Results Fourteen patients were enrolled (10 with neuroblastoma, one with retinoblastoma, one with Wilms' tumor, and two with brainstem glioma). Three patients completed the three drug levels and three were enrolled in the confirmation cohort. One patient died of tumor progression before completing the three applications. Racotumomab was well tolerated. The only side effect observed was grade 1–2 toxicity at the injection site. Racotumomab elicited an IgM and/or IgG antibody response directed against NGcGM3 in nine patients and IgM against racotumomab in 11 of 13 evaluable patients. The maximum tolerated dose was not reached and no dose‐limiting toxicity was seen. Conclusions Racotumomab vaccination has a favorable toxicity profile up to a dose of 0.4 mg, and most patients elicited an immune response. Its activity as immunotherapy for neuroectodermal malignancies will be tested in further clinical trials. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.